Spiritual Marketing dan Experiential Marketing untuk Menjaga Kepercayaan Pelanggan - Rosida, Ika Nazilatur (Program Studi Ekonomi Syariah STAI Senori Tuban, 2025)
Basic English Course (BEC) is the oldest English course institution in Pare. BEC is over 47 years old, but uniquely, this institution has never promoted through any advertisements, including online marketing on any social media. The study aims to analyze and describe the spiritual marketing strategy and experiential marketing in maintaining customer trust as a language course institution in the era of globalization. The study employed a phenomena descriptive approach with observation and correlation. The result of this study found that in maintaining customer trust, BEC is a course institution that is oriented towards quality over quantity. Moreover, it is supported by the experience of alumni and the success of BEC alumni in the community. It became the most effective and efficient marketing channel. The marketing channel is formed naturally and is the concrete form of spiritual marketing and experiential marketing, reflecting how authenticity, sincerity, and shared experience can build long-term trust and sustainability without relying on conventional promotional strategies.